Effects of feeding different level of lupins (Lupinus angustifolius) on growth performance of Boer goats - Mohd Yusof, Ainul Yuzairi; Abu Bakar @ Zakaria, Md Zuki; Ahmad, Yusof Hamali; Goh, Yong Meng; Muhammad Ali, Abu Hassan (2012)
Boer goats (n=24) aged 8-9 month old were used to assess the effects of feeding different level of lupins (Lupinus angustifolius) on growth performance. The goats were divided into 3 groups (n=8) and fed feeding trial for 103 days with total mixed ration (TMR) diets containing different level of Lupin: TMR A (0 % Lupin), TMR B (10 % Lupin) and TMR C (30% Lupin). The final weight, average daily gain (ADG), total weight gain and feed conversion ratio (FCR) for all the experimental groups were similar (P>0.05). However, there was a significant decrease (P<0.05) in the total feed intake (TFI) and dry matter intake (DMI) for the TMR C group compared to the TMR A and B groups. The current results indicate the potential utilization of lupin as protein source in Boer goat feeding.